ROLE OF PALASH (BUTEA MONOSPERMA) KSHARA IN THE MANAGEMENT OF DUSTA VRANA (CHRONIC ULCERS) WITH SPECIAL REFERENCE TO INFECTED WOUND - Gupta, S; Gupta, S J; Singh, S K (International Journal of Ayurveda and Pharma Research, 2015)
Wound infection is one of the most important factors that cause delayed wound healing. Wound healing occurs as a fundamental response to tissue injury. Several natural products have been shown to accelerate the healing process. Dusta vranas (chronic ulcers) are a frequently encountered problem in present era produced commonly as a complication of trauma or pathological insult and it causes long term agony to the patient. The present study was undertaken to determine the efficacy of topical administration of Kshara of stem bark of Palash (Butea monosperma (Lam.) Taub.) on Dusta vrana with special reference to infected wound. These drugs possess Vrana shodhana and Ropana properties. It was used topically in chronic or infected wound once daily for 14 days or till the wound bed is prepared whichever is earlier. It is a clinical study wherein 30 patients were selected and divided in three equal groups of ten patients each. It was found to reduce pain, discharge and slough tissue. It also helped in improved floor and granulation tissue formation that is to prepare wound bed as compared to control group. Hence it can be speculated that Palash kshara possess sufficient efficacy in Vrana shodhana (wound debridement) and Vrana ropana without producing any adverse affects.